Developing a Model of the Role of Security and Social Support in Students’ Extracurricular Activities (Sports–Leisure) and Its Role in Crime Prevention - Sadeghi, Ali; Jahan, Javad; Ahmadi, Ali; Karimi, Ali (Assessment and Practice in Educational Sciences, 2026)
The present study was conducted with the aim of developing a model of the role of security and social support in students’ extracurricular activities (sports–leisure) and its role in crime prevention. In terms of purpose, the study was applied research; in terms of nature, it was descriptive; and in terms of implementation, it employed structural equation modeling. The statistical population consisted of students of Payame Noor University in Kermanshah Province. The samples were selected from among students who, according to reports from the university’s cultural and sports authorities, spent at least one hour of their leisure time on physical and sports activities (155 participants). The sampling method was multi-stage cluster random sampling. Data were collected from students through a standardized questionnaire based on a five-point Likert scale. The reliability of the questionnaire was calculated using Cronbach’s alpha coefficient (0.91), and its validity was confirmed by experts in the field of sports sciences and criminology specialists. The results indicated that security factors and social support significantly influenced the level of students’ extracurricular activities (sports–leisure) in the direction of crime prevention. The findings also revealed that the level and type of security and social support differed among the branches of Payame Noor University in Kermanshah Province. Finally, it was determined that different forms of social support (financial, emotional, and instrumental support) increased students’ participation in sports and leisure activities for the purpose of crime prevention. Therefore, it is recommended that the government and relevant organizations, including the Ministry of Science, Research and Technology and Payame Noor University, reduce security-related barriers and strengthen various forms of social support, such as reducing student tuition fees and improving free university sports facilities, in order to enhance students’ leisure and sports activities.